Hypertension module: An interactive learning tool in physiology - KURTEL, HIZIR; GÜLPINAR, MEHMET ALİ; ALİCAN, YAŞAR İNCİ (AMER PHYSIOLOGICAL SOC, 2003)
The aim of the present study was to evaluate the strong or weak aspects of an interactive study module introduced during the Cardiovascular and Respiratory Systems Subject Committee in the second year of the medical program. Five study groups consisting of 25 students attended two-hour module sessions for six weeks with the same tutor. According to the module assessment questionnaire, the majority of the students assessed the module as excellent or good. The students reported that they had gained not only in knowledge but also in skills development. The general opinion of the students was that both the organization and the implementation of the module met their expectations. Nearly one-half of the students reported that their expectations with regard to the educational environment and the participation of students were fully met. The major weakness in this new educational trial appears to be assessment of the module.
Keywords: physiology education; didactic lectures; small-group study; student feedback